Presumptive thrombotic thrombocytopenic purpura following a hump-nosed viper (Hypnale hypnale) bite: a case report - Withana,Milinda (2014)
Hump-nosed viper bites are frequent in southern India and Sri Lanka. However, the published literature on this snakebite is limited and its venom composition is not well characterized. In this case, we report a patient with thrombotic thrombocytopenic purpura-like syndrome following envenoming which, to the best of our knowledge, has not been reported in the literature before. A 55-year-old woman from southern Sri Lanka presented to the local hospital 12 hours after a hump-nosed viper (Hypnale hypnale) bite. Five days later, she developed a syndrome that was characteristic of thrombotic thrombocytopenic purpura with fever, thrombocytopenia, microangiopathic hemolysis, renal impairment and neurological dysfunction in the form of confusion and coma. Her clinical syndrome and relevant laboratory parameters improved after she was treated with therapeutic plasma exchange. We compared our observations on this patient with the current literature and concluded that thrombotic thrombocytopenic purpura is a theoretically plausible yet unreported manifestation of hump-nosed viper bite up to this moment. This study also provides an important message for clinicians to look out for this complication in hump-nosed viper bites since timely treatment can be lifesaving.